Pengaruh Budaya Organisasi, Lingkungan Kerja Fisik dan Kompensasi Finansial Terhadap Kinerja Karyawan (Studi Kasus pada Karyawan UD. Dua Bidadari Kab. Kediri) - Diahayu Novita Sari; Suseno Hendratmoko; Endah Kurniawati (Universitas 45 Surabaya, 2025)
This thesis research is motivated by a phenomenon. In the era of globalization, business competition within companies is becoming increasingly intense and complex, making the quality of human resources a crucial factor in achieving an organization's objectives. UD. Dua Bidadari is a private company engaged in the sale of building materials for the construction of residential buildings, malls, and educational institutions in Kediri and its surroundings. In addition, UD. Dua Bidadari also accepts orders and provides delivery of materials to customers. The aim of this research is to analyze whether there is an effect of organizational culture, physical work environment, and financial compensation on employee performance at UD. Dua Bidadari in Kediri Regency both partially and whether there is a simultaneous effect of organizational culture, physical work environment, and financial compensation on employee performance at UD. Dua Bidadari in Kediri Regency. This study uses a quantitative approach. The sample used in this study was 40 respondents using the sampling method. This study shows that: 1) The Organizational Culture Variable (X1) partially has a significant effect on employee performance (Y). This can be seen in significant statistical results. t 0.021 > 0.05 means that the alternative hypothesis (Ha) can be proven and accepted, 2) The variable of the physical work environment (X2) partially has a significant influence on employee performance (Y). This can be seen in significant statistical results. t 0.04 < 0.05 means that the alternative hypothesis (Ha) can be proven and accepted, 3) The financial compensation variable (X3) has no effect on employee performance (Y). This can be seen in the significant statistical results. t 0.127 > 0.05 means that the alternative hypothesis (Ha) can be proven and rejected, 4) The variables of organizational culture (X1), physical work environment (X2) and financial compensation (X3) have a significant effect on employee performance (Y) simultaneously. This can be seen in the statistical results with a significant value of F of 0.005 < 0.05, meaning that simultaneously there is a significant influence between organizational culture (X1), physical work environment (X2) and financial compensation (X3) on employee performance (Y) in UD. Two Angels of Kediri Regency.